The Role of the School Library in Achieving Cultural Development in the Light of Contemporary Technological Variables among Secondary School Students from the Teachers’ Point of View in Taif - Alamrity, Eman Ibrahem; Alfaifi, Najah Yahya (Journal of Educational and Psychological Sciences, 2025)
This study aims at identifying the role of the school library in achieving the cultural development of secondary students and the extent to which it conforms to contemporary technological changes. The descriptive approach was used to achieve the objectives of the study. A questionnaire was used to collect data, which included three fields: the reality of using the school library, the relationship of the school library to cultural development, and the relationship of the school library to technology. The sample consisted of (447) secondary school teachers in Taif. The results showed that the use of the school library among secondary school students from the teachers’ point of view came to a medium degree, and that the relationship between the school library and cultural development in the light of the changes in contemporary technology in the secondary school students from the teachers’ point of view came to a medium degree, and the school library relationship with technology came to a medium degree. The results indicated that there were no statistically significant differences at the level of (α≤0.05) on the fields (the reality of using the school library, the relationship of the school library to development, and the relationship of the school library to technology) and the tool as a whole depending on the variables of the school building, type of school and experience. In light of the results of the study, the researcher recommended the need to pay attention to school libraries and their components and provide ventilation, lighting and appropriate furniture, and modern technologies.